A universal-mode chaotic oscillator - Klomkarn, Kitdakorn; Sooraksa, Pitikhate (My University, 2019)
The universal-mode chaotic oscillator obtaining various pattern chaotic signals is presented. In the proposed circuit, fours current feedback operational amplifiers(CFOAs) and one conventional operational amplifier are designed and implemented. The proposed circuits are verified by Pspice simulation and are validated by experiments.
Keywords: Analog Sgnal Synthesis; Chaos application; Chaotic oscillator